Expressão local e sistêmica da ativina A e folistatina e seus efeitos biológicos in vitro na endometriose - Ana Luiza Lunardi Rocha Baroni (2011)
Objective: To evaluate the expression pattern of activin A, activin receptors, and activin modulators messenger RNA (mRNA) in the eutopic endometrium of patients with endometriosis at different phases of the menstrual cycle and to evaluate the mRNA expression of the same proteins in endometriomas during the menstrual cycle. Activin A is a growth factor produced by the endometrium, whose actions are modulated by the binding protein follistatin. Both proteins are detectable in peripheral serum, raising the potential for novel serum markers of endometriosis. The study aimed to evaluate the effect of activin A and follistatin on interleukin (IL)-6, IL-8 and vascular endothelial growth factor (VEGF) secretion from cultured human endometrial stromal cells from women with and without endometriosis. Material and Methods: Design: Prospective study. Setting: University hospital. Patient(s): Women with and without endometriosis and Human endometrial stromal cells (HESC) treated with activin A at different doses with/without follistatin. Methods: Quantification of activin A, activin B, activin receptor II, nodal, cripto, inhibin a, and follistatin expression by real-time reverse-transcriptase polymerase chain reaction (RT-PCR). Multicenter controlled study evaluating simultaneously serum activin A and follistatin concentrations in women with and without endometriosis. Quantification of IL-6, IL-8 and VEGF by real time polymerase chain reaction and measurement of these cytokines and VEGF secretion by ELISA. Results: The eutopic endometrium of patients with endometriosis showed (1) higher activin A mRNA expression in the proliferative phase and a lack of late secretory phase peak, (2) a lack of endometrial cycle-related variations of cripto and inhibin a mRNA expression, and (3) an inverse expression pattern of follistatin mRNA. Endometriomas showed similar variations in the expression of activin-related protein mRNA during the menstrual cycle as eutopic endometrium. The ovarian endometrioma group had serum activin A levels significantly higher than healthy controls (0.22 ± 0.01 ng/ml vs. 0.17 ± 0.01 ng/ml, p<0.01). None of the endometriosis groups had serum follistatin levels significantly altered compared to healthy controls, while levels found in the endometrioma group (2.34 ± 0.32 ng/ml) were higher than in the deep endometriosis group (and 1.50 ± 0.17 ng/ml, p<0.05). The area under the ROC curve of activin A was 0.700 (95% confidence interval 0.605-0.794), while that of follistatin was 0.620 (0.510-0.730) for the diagnosis of ovarian endometrioma. The combination of both markers into a duo marker index did not improve significantly their diagnostic accuracy. At baseline, IL-6, IL-8 and PGE2 secretion were higher in endometriosis group. Activin A increased IL-8 and VEGF secretion in HESc from controls but decreased IL-6 and IL-8 secretion in HESC from women with endometriosis. These results were abrogated by follistatin. Conclusions: The disturbed expression of endometrial activin A, cripto (activin receptor antagonist), and follistatin (activin-binding protein) suggests a dysfunction of the activin pathway in endometriosis. Endometriomas showed similar changes of activin-related proteins during the menstrual cycle, which supports a common biology for eutopic and ectopic endometrium in endometriosis. The present study demonstrated that serum activin A and follistatin do not change significantly in peritoneal or deep infiltrating endometriosis and have limited diagnostic accuracy in the diagnosis of ovarian endometrioma. The present study showed for the first time that activin A regulates the expression and secretion of cytokines and VEGF in a different way in cultured endometrial stromal cells from controls and patients with endometriosis, supporting several possible sites of activin action in the pathogenesis of endometriosis